2018
DOI: 10.1016/j.bcp.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine promotes cellular iron accumulation and oxidative stress responses in macrophages

Abstract: Iron is essential for many biological functions including neurotransmitter synthesis, where the metal is a co-factor of tyrosine hydroxylase, which converts tyrosine to dopamine and further to norepinephrine. As the shared chemical structure, called catechol, may potentially bind iron we questioned whether tyrosine derived hormones would impact on cellular iron homeostasis in macrophages, which are central for the maintenance of body iron homeostasis. Using murine bone marrow-derived macrophages (BMDMs), we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 54 publications
4
55
0
Order By: Relevance
“…Importantly, we found that RLS patients treated with dopaminergic drugs had significantly improved mitochondrial respiratory capacity compared with patients without treatment. Based on previous studies indicating that dopaminergic molecules such as neuromelanin affect iron homeostasis and the regulation of iron transporters and in agreement with our recent observation that dopamine directly increases cellular iron accumulation, these data would indicate that the beneficial effect of l ‐dopa or dopamine agonists is partially related to an increase in intracellular iron availability, thereby ameliorating mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we found that RLS patients treated with dopaminergic drugs had significantly improved mitochondrial respiratory capacity compared with patients without treatment. Based on previous studies indicating that dopaminergic molecules such as neuromelanin affect iron homeostasis and the regulation of iron transporters and in agreement with our recent observation that dopamine directly increases cellular iron accumulation, these data would indicate that the beneficial effect of l ‐dopa or dopamine agonists is partially related to an increase in intracellular iron availability, thereby ameliorating mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is an essential component in neurotransmitter synthesis, where the metal is a co-factor of tyrosine hydroxylase, which converts tyrosine to DA and further to norepinephrine. The chemical compound, called catechol, may potentially bind iron [ 34 ]. An excess of iron may lead to a vast increase in the production of free radicals, which overwhelms the natural defensive mechanisms and causes damage at several cellular levels.…”
Section: Parkinson’smentioning
confidence: 99%
“…A study using murine bone marrow-derived macrophages showed that dopamine affected cellular iron homeostasis by increasing the uptake of non-transferrin bound iron. It resulted in intracellular oxidative stress responses and increased the transcriptional expression of stress response genes such as heme oxygenase-1 and the iron export protein ferroportin [ 34 ]. Also, the iron released from Neuromelanin (NM) increases oxidative stress in mitochondria, disrupting its function and reducing ATP-dependent proteasomal activity of 26S (the proteasome involved in the ubiquitin system) [ 36 ].…”
Section: Parkinson’smentioning
confidence: 99%
“…Regarding AMPH, it did not cause significant changes in zebrafish social behavior, replicating what is known for rodents. PCA and clustering analysis suggest that in fact, both open tank and social interaction tests have sufficient resolution to identify distinct behavioral phenotypes related to schizophrenia in zebrafish models, specially following MK-801 exposure.Studies in rodent models report that increased dopamine release induced by AMPH promotes oxidative stress, probably due to increase monoamine metabolism(Dichtl et al, 2018;El-Tawil et al, 2011;Frey et al, 2006). All tested concentrations of AMPH increased TBARS, a well-established marker of lipid peroxidation, after 60 min, but not after 10 min of exposure, indicating a time-depend effect on the production of…”
mentioning
confidence: 84%